Analisis Penerapan Praktik Lapangan Dalam Perbaikan dan Perawatan Pressure Control Equipment di Perusahaan Net - Christopher, Dave (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Pressure Control Equipment (PCE) is a vital piece of equipment in the oil and gas industry that controls fluid pressure to ensure operational safety. PCE malfunction can lead to leaks, work accidents, and even operational losses. This study aims to analyze the application of field practices in Pressure Control Equipment repair and maintenance activities at Net Company, specifically the Hydrostatic test (hydrotest) method. The study was conducted through direct observation at Net Company's workshop, in the form of pressure test data analysis. The results of the study indicate that the PCE maintenance and testing process has been carried out in accordance with API SPEC 6A standards. Hydrotest testing at low, medium, and high pressures showed pressure stability without any leaks, so the equipment was declared operationally fit. The conclusion of this study shows that the implementation of systematic and standardized field practices plays a very important role in maintaining equipment reliability and safety in oil and gas operations.